Đóng góp của tâm lý học Vưgốtxki cho lý thuyết học ngôn ngữ thứ hai - Lê, Văn Canh (H. : ĐHQGHN, 2017)
In recent decades, many studies on second of foreign language acquisition have been undertaken worldwide within the framework of Vygotskian psychology. This paper highlights the contributions of Vygotskian psychology or the socio -cultural psychology with its central concepts of the zone of proximal development and social interaction asa psychological tool in the child's cognitive development to the insights into the nature of second language learning.